The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5397/cise.2019.00416
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Options for Failed Rotator Cuff Repair, except Arthroplasty: Review of Current Methods

Abstract: Although the prevalence of rotator cuff tears is dependent on the size, 11% to 94% of patients experience retear or healing failure after rotator cuff repair. Treatment of patients with failed rotator cuff repair ranges widely, from conservative treatment to arthroplasty. This review article attempts to summarize the most recent and relevant surgical options for failed rotator cuff repair patients, and the outcomes of each treatment, except arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 94 publications
(101 reference statements)
0
13
0
Order By: Relevance
“…Recently, the techniques and instrumentation used for surgical repair of torn rotator cuffs have rapidly improved, and the clinical and functional outcomes of rotator cuff repair have been satisfactory. 2 , 25 Nevertheless, large to massive RCTs are still a formidable and challenging problem, 18 , 26 , 43 and in some large to massive RCTs, the direct repair of the native rotator cuff tendons to the footprint of the greater tuberosity is impossible, even after adequate release, because of retraction, attenuation, and inelasticity of tendons. 4 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the techniques and instrumentation used for surgical repair of torn rotator cuffs have rapidly improved, and the clinical and functional outcomes of rotator cuff repair have been satisfactory. 2 , 25 Nevertheless, large to massive RCTs are still a formidable and challenging problem, 18 , 26 , 43 and in some large to massive RCTs, the direct repair of the native rotator cuff tendons to the footprint of the greater tuberosity is impossible, even after adequate release, because of retraction, attenuation, and inelasticity of tendons. 4 …”
mentioning
confidence: 99%
“…Recently, the techniques and instrumentation used for surgical repair of torn rotator cuffs have rapidly improved, and the clinical and functional outcomes of rotator cuff repair have been satisfactory. 2,25 Nevertheless, large to massive RCTs are still a formidable and challenging problem, 18,26,43 and in some large to massive RCTs, the direct repair of the native rotator cuff tendons to the footprint of the greater tuberosity is impossible, even after adequate release, because of retraction, attenuation, and inelasticity of tendons. 4 Many surgical procedures have been introduced for the treatment of irreparable RCTs: arthroscopic debridement, 27 tuberoplasty, 16,54 partial repair, 3 interposition grafting (IG), 41,46 superior capsular reconstruction (SCR), 34 tendon transfers, 15,17 reverse total shoulder arthroplasty, 6,39,50 and arthrodesis.…”
mentioning
confidence: 99%
“…26 Although surgical techniques and instrumentation have developed considerably in the past years, the failure rate of rotator cuff healing after repair is still high and an unsolved problem. 11,15,22,25 Transforming growth factor beta 1 (TGF-b1) is a protein that performs many cell functions, including the control of cell growth, cell proliferation, cell differentiation, and apoptosis. 4,36 Previous studies have shown that TGF-b1 is a major mediator in the healing phase, facilitating collagen production, angiogenesis, and extracellular matrix formation.…”
mentioning
confidence: 99%
“…26 Although surgical techniques and instrumentation have developed considerably in the past years, the failure rate of rotator cuff healing after repair is still high and an unsolved problem. 11,15,22,25…”
mentioning
confidence: 99%
“…For these reasons, MRI is the investigation of choice to evaluate a suspected re-tear following rotator cuff repair. 42…”
Section: Investigationmentioning
confidence: 99%